Respostas ecofisiológicas e bioquímicas do Pajeú (Triplaris gardneriana Wedd.) submetido ao déficit hídrico - Queiroz, Jéssica Chapeleiro Peixoto (2018)
Water is essential to the survival of plants. Reductions in availability, caused by high evaporative demand and/or supply limitation, can lead to numerous morphophysiological changes in the plant. The Caatinga biome, located in the Brazilian semi-arid region, is characterized by an irregular rainfall regime associated with high temperatures, causing, therefore, situations of water deficiency to the plants that live there. Occurring naturally in the Caatinga, especially associated with the São Francisco River, in floodplain and humid slopes of the Matogrossense pantanal, the pajeuzeiro is a tree that has important importance in the ornamentation, popular medicine, wood supply and restoration of degraded areas. The mechanisms used by the pajeuzeiro to survive in situations of water deficit are still scarce. In view of this, the present work had the objective of investigating physiological and biochemical changes of the pajeuzeiro when submitted to the water deficit, as well as its capacity of recovery after the rehydration. For this, a greenhouse experiment was carried out in a completely randomized design, with four treatments to recover water lost by evapotranspiration (T100 - control, T50 - 50%, T25 - 25% and T0 - without replacement) repetitions each. Leaf water potential (Ψw), relative water content (TRA), foliar protoplasm tolerance, gas exchange (gs, E, A and WUE), as well as chlorophyll fluorescence a were evaluated. For the biochemical analyzes, the content of photosynthetic pigments (Chl a, Chl b, total Chl and carotenoids), soluble proteins, free proline and carbohydrates were analyzed. The Pajeuzeiro was affected by the water deficit, with a significant reduction in its Ψw and TRA, which reached values below 60%. In addition, significant reductions in stomatal conductance (gs), transpiration (E), photosynthetic rate (A), quantum efficiency of PSII (Fv/Fm), area and performance index (PIABS) were observed in treatments under water deficit. As the water deficit intensified, an increase in the percentage of membrane damage was observed, with T0 presenting the highest damage index in relation to the control. The restriction in water availability also significantly affected the concentration of photosynthetic pigments, with reductions for chl a, b and total and increase for carotenoids. In addition, the deficit promoted a significant increase in the concentration of soluble proteins for T0 and T25 and of free proline for the three treatments with water deficiency. For the carbohydrate concentration, there was an increase, but not significant. The pajeuzeiro was strongly affected by the water deficit, but demonstrated a strong recovery capacity of all parameters analyzed after rehydration, which shows a certain degree of tolerance of the species. Therefore, the Triplaris gardneriana species uses stomatal closure, along with leaf senescence and abscision, as the main mechanism to prevent excessive water loss.